Genome-wide identification of drought-responsive microRNAs in two sets of Malus from interspecific hybrid progenies. Issue 1 (8th June 2019) - Niu, Chundong; Li, Haiyan; Jiang, Lijuan; Yan, Mingjia; Li, Cuiying; Geng, Dali; Xie, Yinpeng; Yan, Yan; Shen, Xiaoxia; Chen, Pengxiang; Dong, Jun; Ma, Fengwang; et al.
Abstract: Drought stress can negatively impact apple fruit quality and yield. Apple microRNAs (miRNAs) participate in apple tree and fruit development, as well as in biotic stress tolerance; however, it is largely unknown whether these molecules are involved in the drought response. To identify drought-responsive miRNAs in Malus, we first examined the drought stress tolerance of ten F1 progenies of R3 ( M . ×  domestica ) ×  M. sieversii . We performed Illumina sequencing on pooled total RNA from both drought-tolerant and drought-sensitive plants. The sequencing results identified a total of 206 known miRNAs and 253 candidate novel miRNAs from drought-tolerant plants and drought-sensitive plants under control or drought conditions. We identified 67 miRNAs that were differentially expressed in drought-tolerant plants compared with drought-sensitive plants under drought conditions. Under drought stress, 61 and 35 miRNAs were differentially expressed in drought-tolerant and drought-sensitive plants, respectively. We determined the expression levels of seven out of eight miRNAs by stem-loop qPCR analysis. We also predicted the target genes of all differentially expressed miRNAs and identified the expression of some genes. Gene Ontology analyses indicated that the target genes were mainly involved in stimulus response and cellular and metabolic processes. Finally, we confirmed roles of two miRNAs in apple response to mannitol. Our results reveal candidate miRNAs and their associated mRNAs that could be targeted for improving drought tolerance in Malus species, thus providing a foundation for understanding the molecular networks involved in the response of apple trees to drought stress.